Land Covers Change and Its Impact to Carbon Stocks in Ciliwung Watershed - Basuki Wasis; Bambang Hero Saharjo; Hadi Susilo Arifin; Arief Nugroho Nur Prasetyo (Jurnal Silvikultur Tropika, 2012)
Land  cover  changes will affect the ecological condition of  the watershed.  Currently, the  conversion of  natural forests into agricultural land has been one of  the main  causes of  deforestation  in  Indonesia. The  changes  could  give impact to  erosion,  increased  run off  and  sedimentation,  loss of  biodiversity,  change of micro  climate,  the release of carbon and Green House Gas (GHG) into the air, etc. This problem has been going on in Watershed Ciliwung.  Forest area, as sources of carbon deposits and carbon absorbents, has limited area along with increasing extents of build up areas. Therefore, it’s estimated the ecological changes will be extended, then will affect the amount of carbon  stocks in Watershed Ciliwung. The objectives of research are  to determine  land cover changes during  the  last twenty years,  to analyze actual carbon stocks in watershed Ciliwung, and to analyze the effect of land cover changes in over twenty years of greenhouse gases, especially CO2. This research used three samples plot on each of the existing land cover. Biomass approach was used in order to estimate carbon stock. Changes in carbon stocks were calculated by using interpolation based on  the actual  carbon  stocks  in 2011. The  research  results  showed  that build up areas was  increased  153,36% during twenty years. The highest potencial carbon stocks was  found in pines forests, which is 144,99 tons/ha. Over the last twenty years, carbon stocks in watershed Ciliwung is declined 42.329,75 tons carbon or 155.350,182 tons CO2e.